Determination of critical angle of circumferential throughwall crack for structurally distorted 90° pipe bends under bending moment with and without internal pressure. (May 2019) - Sumesh, S; Veerappan, AR; Shanmugam, S
Throughwall circumferential cracks (TWC) in elbows can considerably minimize its collapse load when subjected to in-plane bending moment. The existing closed-form collapse moment equations do not adequately quantify critical crack angles for structurally distorted cracked pipe bends subjected to external loading. Therefore, the present study has been conducted to examine utilizing elastic-plastic finite element analysis, the influence of structural distortions on the variation of critical TWC of 90° pipe bends under in-plane closing bending moment without and with internal pressure. With a mean radius ( r ) of 50 mm, cracked pipe bends were modeled for three different wall thickness, t (for pipe ratios of r / t  = 5, 10, 20), each with two different bend radius, R (for bend ratios of R/r = 2, 3) and with varying degrees of ovality and thinning (0 to 20% with increments of 5%). Finite element analyses were performed for two loading cases namely pure in-plane closing moment and in-plane closing bending with internal pressure. Normalized internal pressures of 0.2, 0.4, and 0.6 were applied. Results indicate the modification in the critical crack angle due to the pronounced effect of ovality compared to thinning on the plastic loads of pipe bends. From the finite element results, improved closed-form equations are proposed to evaluate plastic collapse moment of throughwall circumferential cracked pipe bends under the two loading conditions.